DAMPAK PANDEMI COVID-19 TERHADAP PEREKONOMIAN KEPULAUAN RIAU - Hardiansyah, Raja; Tanjung, Rona; Ifardiyanto, Ifardiyanto (BENING, 2021)
AbstrakCOVID-19 adalah penyakit menular yang disebabkan oleh jenis baru dari virus corona selain telah menyebabkan krisis kesehatan, juga berdampak pada perekonomian, tidak hanya secara nasional namun juga ke seluruh provinsi di Indonesia termasuk Kepulauan Riau. Maka dari itu tujuan dari penelitian ini adalah untuk mengetahui dampak pandemi COVID-19 terhadap perekonomian Kepulauan Riau. Pendekatan penelitian yang digunakan adalah deskriptif kualitatif dengan metode kepustakaan berupa pengumpulan data-data dokumen, jurnal, laporan-laporan yang diterbitkan oleh lembaga resmi yang yang terkait dengan indikator perekonomian Kepulauan Riau yakni pertumbuhan ekonomi sisi pengeluaran dan pertumbuhan ekonomi berdasarkan lapangan usaha.. Hasil penelitian ini menunjukkan terjadinya perlambatan perekonomian global dan nasional akibat pandemi COVID-19 juga berdampak pada perekonomian Kepulauan Riau. Hal tersebut dapat dilihat dari terkontraksinya pertumbuhan ekonomi dan komponen perekonomian Kepulauan Riau baik itu sisi pengeluaran maupun dari sisi lapangan usaha. Selain itu dampak COVID-19 juga menyebabkan pergerakan laju inflasi di Kepulauan riau berjalan tidak seperti biasa. Pemulihan ekonomi diharapkan dapat berfokus dengan membangun dan memperkuat sektor usaha yang menjadi pengungkit ekonomi demi tercapainya penggerak ekonomi masyarakat di daerah.Kata Kunci : Perekonomian, PDRB, Covid-19Â AbstractCOVID-19 is an infectious disease caused by a new type of corona virus, besides causing a health crisis, it also has an impact on the economy, not only nationally but also to all provinces in Indonesia including the Riau Islands. Therefore the aim of this study is to determine the impact of the COVID-19 pandemic on the economy of the Riau Islands. The research approach used is descriptive qualitative with the literature method in the form of collecting document data, journals, reports published by official institutions related to the economic indicators of the Riau Islands, namely economic growth on the expenditure side and economic growth based on business fields. The data is then processed and presented in graphic form and equipped with descriptive narratives related to the impact of the COVID-19 pandemic on the economy of the Riau Islands. The results of this study indicate that the global and national economic slowdown due to the COVID-19 pandemic also has an impact on the economy of the Riau Islands. This can be seen from the contraction of economic growth and economic components of the Riau Islands, both from consumption side and production side. In addition, the impact of COVID-19 has also caused the inflation rate movement in the Riau Islands to run abnormally. It is hoped that this economic recovery can focus on building and strengthening the business sector which become trigger of the economy in order to achieve the economic driver of the community in the regionsKeywords: Economy, GRDP, Covid-19